Psychology applied to modern life adjustment in the 21st century - Weiten, Wayne; Dunn, Dana; Hammer, Elizabeth Yost (Cengage Learning, 2015)
Filled with coverage of classic and contemporary research, relevant examples, and engaging applications, this text shows students how psychology helps them understand themselves and the world - and uses psychological principles to illuminate the variety of opportunities they have in their lives and their future careers.